Studies of transferrin in serum of workers exposed to organic solvents. Issue 8 (August 1987) - Petrén, S; Vesterberg, O
Abstract : Earlier studies have shown that determination of the serum concentration of different forms of transferrin (isotransferrins) may be used to detect hepatic effects caused by alcohol abuse. The isotransferrin variant with an isoelectric point of 5.7 has been compared with the total amount of serum transferrin in order to study hepatic effects caused by occupational exposure to organic solvents. Eighteen workers from a paint industry were tested before and after their holiday and compared with two different groups, a total of 60 subjects. The solvent workers had significantly higher values both before and after their holiday. This suggests that the effects on the liver caused by organic solvents are similar to those caused by alcohol abuse and that this is a long term effect. The level of exposure to organic solvents was below the Swedish threshold limit values.